The effect of long-acting paliperidone palmitate once-monthly on negative and depressive symptoms in patients with schizophrenia switched from previous unsuccessful treatment with oral aripiprazole - Schreiner, Andreas (Ther Adv Psychopharmacol, 2016)
BACKGROUND: The negative symptoms of schizophrenia are generally harder to recognize, more difficult to treat than positive symptoms, and have a significant impact on patient functioning and overall outcomes. Treatment with aripiprazole may be associated with benefits on negative symptoms and functioning given its partial agonism to the dopamine D(2) receptor. The aim of this subanalysis was to explore the impact of flexibly dosed, long-acting paliperidone palmitate once monthly (PP1M) on negative and depressive symptoms, disorganized thoughts, anxiety, extrapyramidal symptoms, and patient functioning in nonacute adult patients with schizophrenia previously unsuccessfully treated with oral aripiprazole monotherapy. METHODS: Post-hoc subanalysis of 46 nonacute but symptomatic patients enrolled in a prospective, interventional, single-arm, multicenter, open-label 6-month study. RESULTS: At endpoint, improvements of ⩾ 20% and ⩾ 50% in the Positive and Negative Syndrome Scale (PANSS) total score were observed in 52.2% and 21.7% of patients, respectively. Significant and clinically relevant improvements were observed at endpoint in mean (standard deviation [SD]) PANSS negative subscale score (−3.0 (5.0); p < 0.0001) and in the PANSS Marder factor scores for negative symptoms (−2.9 (5.4); p = 0.0006), disorganized thoughts (−2.8 (4.3); p < 0.0001) and anxiety/depression (−1.8 (3.9); p = 0.0031). Patient functioning assessed by mean (SD) Personal and Social Performance scale score (3.9 (13.2); p = 0.0409), Mini International Classification of Functioning rating for Activity and Participation Disorders in Psychological Illnesses total scores (−2.9 (7.1); p = 0.0079), and Extrapyramidal Symptom Rating Scale scores (−0.6 (3.4); p = 0.0456) improved significantly at endpoint. PP1M was well tolerated with no new safety signals. CONCLUSIONS: Six-month treatment with flexibly dosed PP1M was associated with significant and clinically relevant improvements in negative and depressive symptoms, disorganized thoughts, functioning, and extrapyramidal symptoms in nonacute but symptomatic patients with schizophrenia previously unsuccessfully treated with oral aripiprazole.